PROSPEK ENZIM DAN LIMBAH LIGNOSELULOSA UNTUK PRODUKSI BIOETANOL - Trisanti Anindyawati (JURNAL SELULOSA, 2009)
Substitution bioethanol as one of energy source has been selected as an alternative source for the fossil fuel substitution. The arricultural and industrial waste can be used for the production of bioethanol. The main component in those waste materials is lignocelluloses that contained cellulose, hemicelluloses and lignin. Lignocellulose will be the main source for bioethanol production in the long term. Several enzymes have been recorded in degrading lignollulose wich are cellulolytic, hemicellulolytic as well as lignolytic. The main enzyme which has the most important role in bioethanol production are complex enzyme which degrade lignocelluloses. Bioethanol prodaction is much affected by raw materials composition, type of microorgranisms, and the fermentation condition used.Key words: lignocelluloses, cellulase, hemicellulase, lignin degrading enzyme, bioethanolINTISARI Bioetanol merupakan salah satu energy alternative pengganti minyak bumi. Bahan limbah pertanian dan industry dapat digunakan untuk produksi bioetanol. Komponen utama pada limbah pertanian dan industri yang digunakan untuk produksi bioetanol adalah lignoselulosa yang terdiri dari selulosa, hemiselulosa dan lignin. Lignoselulosa merupkan bahan utama produksi bioetanol untuk jangka panjang. Enzim yang berperan dalam degradasi lignoselulosa adalah enzim yang bersifat selulotik, hemiselulolitik dan lignolitik. Enzim utama yang berperan penting pada produksi bioetanol merupakan enzim kompleks yang mampu mendegradasi lignoselulosa. Produksi bioetanol sangat di pengaruhi oleh komposisi bahan baku, jenis mikroorganisma dan kondisi fermentasi yang digunakan.Kata Kunci : lignoselulosa, selulase, hemiselulase, enzim pendegradasi lignin, bioetanol